2007
DOI: 10.1159/000108940
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Scan for Quantitative ACE Activity in Taiwan Young-Onset Hypertension Study

Abstract: Objectives: Angiotensin converting enzyme (ACE) plays major roles in the pathogenesis of cardiovascular diseases (CVD). However, findings on the relations between ACEvariants and CVD have not been consistent. The purpose of this study was to map quantitative trait loci (QTL) for serum ACE activity, a heritable endophenotype of cardiovascular diseases (estimated heritability = 0.58). Methods: With 1,271 individuals from 373 young-onset (age ≤40) hypertension pedigrees, 479 deCODE microsatellite markers were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…By using the Han Chinese SNP database with SNPbrowser software (Applied Biosystems), we selected 41 SNPs (distributed over ACE and another 11 genes) based on Assay-on-Demand (Applied Biosystems) with a minor allele frequency (MAF) of 0.2 or more (data not shown) within and around the ACE gene and within 1 cM of the highest two-point and multipoint LOD scores from the results of our previous study [17]. Association tests showed that only one (rs4353) out of six SNPs (rs4293, rs4295, rs4353, rs4575595, rs11868324, and rs4267385) located in the ACE gene was statistically significant after Bonferroni correction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the Han Chinese SNP database with SNPbrowser software (Applied Biosystems), we selected 41 SNPs (distributed over ACE and another 11 genes) based on Assay-on-Demand (Applied Biosystems) with a minor allele frequency (MAF) of 0.2 or more (data not shown) within and around the ACE gene and within 1 cM of the highest two-point and multipoint LOD scores from the results of our previous study [17]. Association tests showed that only one (rs4353) out of six SNPs (rs4293, rs4295, rs4353, rs4575595, rs11868324, and rs4267385) located in the ACE gene was statistically significant after Bonferroni correction.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, following up on our previous genomewide scan study [17] we set out to map QTLs for serum ACE activity and to examine their effects on hypertension by analysis of variance approach and measured haplotype analysis. We employed a two-stage approach using, first, data from a Taiwan young-onset hypertension family study and, second, information from an Academia Sinica multi-center study of young-onset hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded angiotensin I-converting enzyme and lipoprotein lipase genes that have been extensively studied in our group. 14,17,18 We also excluded angiotensin II receptor (AGTR2) gene that showed no association in our recent pooling case-control study. In total, we selected 36 candidate genes among which AGT, AGTR1, CYP11B2, GNB3, NOS3, and ADD1 have ≥20 papers recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Although clinical profile and candidate gene studies have sketched a blueprint for genetic susceptibility in YOH in the Han Chinese population [12][15], meticulous dissection of YOH by a systematic genome-wide association study has not been performed. This study aims to identify YOH susceptibility genes for the Han Chinese population based on a two-stage study design consisting of a genome-wide association study (GWAS) and a confirmatory association study (CMAS).…”
Section: Introductionmentioning
confidence: 99%